How do Non-Monetary Performance Incentives for Physicians Affect the Quality of Medical Care? A Laboratory Experiment - Nadja Kairies-Schwarz; Miriam Krieger (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
In recent years, several countries have introduced non-monetary performance incentives for health care providers to improve the quality of medical care. Evidence on the effect of non-monetary feedback incentives, predominantly in the form of public quality reporting, on the quality of medical care is, however, ambiguous. This is often because empirical research to date has not succeeded in distinguishing between the effects of monetary and non-monetary incentives, which are usually implemented simultaneously. We use a controlled laboratory experiment to isolate the impact of non-monetary performance incentives: subjects take on the role of physicians and make treatment decisions for patients, receiving feedback on the quality of their treatment. The subjects decisions result in payments to real patients. By giving either private or public feedback we are able to disentangle the motivational effects of self-esteem and social reputation. Our results reveal that public feedback incentives have a significant and positive effect on the quality of care that is provided. Private feedback, on the other hand, has no impact on treatment quality. These results hold for medical students and for other students.
Keywords: I11; C91; L15; 330